News media's position-taking regarding the European Union: the synchronization of mass media's reporting and commentating in the 2014 European Parliament elections. Issue 1 (2nd January 2019) - Adam, Silke; Eugster, Beatrice; Antl-Wittenberg, Eva; Azrout, Rachid; Möller, Judith; de Vreese, Claes; Maier, Michaela; Kritzinger, Sylvia
ABSTRACT: We analyse whether a newspaper's editorial position regarding the European Union is related to its selection decisions in the news section. We ask whether such a synchronization between news and editorials exists, whether it is conditioned by the type of media system and under which conditions it also affects the selection of transnational voices. Our study is based on a quantitative content analysis of the quality press in seven European countries (Austria, France, Germany, Greece, The Netherlands, Portugal and the United Kingdom) in the run-up to the 2014 European Parliament elections. Our results support a synchronization between editorials and news, specifically with regard to the selection of national speakers. With regard to transnational speakers, they are selectively chosen by a medium if its editorial position is not supported at the national level. Furthermore, they are used to put forward a portrayal of a political community in accordance with the editorial line.